Genetic Variation and Population Structure of the Old World Bollworm Helicoverpa armigera (Hübner, 1808) (Lepidoptera: Noctuidae) in Ethiopia. Issue 4 (7th July 2022) - Fite, Tarekegn; Tefera, Tadele; Husemann, Martin; Getaneh, Gezahegne; Villinger, Jandouwe
Abstract: Helicoverpa armigera is one of the most destructive insect pests of economically valuable crops in the world. Despite its economic importance, the population genetic structure of this insect remains unexplored in Ethiopia. To investigate the genetic diversity and population structure of H. armigera, we sampled 170 individuals from 15 populations throughout Ethiopia. We sequenced a fragment of the mitochondrial cytochrome b ( cyt b ) gene and five exon-primed intron-crossing (EPIC) markers. Twenty cyt b haplotypes with low-to-moderate haplotype diversity (mean Hd = 0.537) and high nucleotide diversity (mean Pi = 0.00339) were identified. The most frequently observed and widely distributed cyt b haplotype was designated as Hap_1 (67.058%), which is identical to sequences found across the globe. Tajima's D and Fu's F for the cyt b data were negative, supporting a model of population expansion. Within populations, a mean of 2.493 alleles/locus was recorded across the five EPIC loci, ranging from 1.200 to 3.600 alleles/locus. The highest mean effective number of alleles/population was 2.369 and the lowest was 1.178. The mean observed heterozygosity ( H O ) of the five loci (0–0.289; mean 0.104 ± 0.020) was lower than the expected heterozygosity ( H E ) (0.095–0.523; mean 0.258 ± 0.028). AMOVA detected significant genetic structure with 61% of the total molecular genetic variation of EPIC genotypes occurring between populations, suggesting a considerable degree of differentiation among populations. STRUCTURE analyses clustered the H. armigera populations into three distinct population groups but very low isolation by distance ( R 2 = 0.0132, P < 0.05).